2022
DOI: 10.3389/fimmu.2022.980709
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to overcome DC dysregulation in the tumor microenvironment

Abstract: Dendritic cells (DCs) play a key role to modulate anti-cancer immunity in the tumor microenvironment (TME). They link innate to adaptive immunity by processing and presenting tumor antigens to T cells thereby initiating an anti-tumor response. However, subsets of DCs also induce immune-tolerance, leading to tumor immune escape. In this regard, the TME plays a major role in adversely affecting DC function. Better understanding of DC impairment mechanisms in the TME will lead to more efficient DC-targeting immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 171 publications
2
18
0
Order By: Relevance
“…Non-responders patients are characterized by higher infiltration by myeloid subsets, including DC cell resting and macrophages. This is in line with studies showing that immune resistance following ICB may be mediated by myeloid subsets (22)(23)(24). Here, we show that non-responders to ICB are characterized by an increase in immunoregulatory ADORA2A gene expression in CD8+ T cell, M1 and M2 clusters.…”
Section: Discussionsupporting
confidence: 92%
“…Non-responders patients are characterized by higher infiltration by myeloid subsets, including DC cell resting and macrophages. This is in line with studies showing that immune resistance following ICB may be mediated by myeloid subsets (22)(23)(24). Here, we show that non-responders to ICB are characterized by an increase in immunoregulatory ADORA2A gene expression in CD8+ T cell, M1 and M2 clusters.…”
Section: Discussionsupporting
confidence: 92%
“…Various immunosuppressive factors are also present in WTLs, which inhibit DC maturation and T cell activation. 30,540 To overcome these issues, extracellular vesicles (EVs) produced by tumor cells have recently been shown to be a vaccination platform that supports DC maturation and neoantigen presentation. Tumor cell-derived EVs can deliver tumor antigen repertoires into DCs and facilitate neoantigen cross-presentation.…”
Section: Determination and Monitoring Of Neoantigen-specific T Cell R...mentioning
confidence: 99%
“…On the other hand, dendritic cells that have arisen from the myeloid linage are known to be pro-inflammatory and, thus, support antitumor immunity [ 162 ]. Additionally, it has been shown that tumor cells within the brain are capable of inhibiting the maturation of DC [ 163 ]. This prevents them from proper antigen presentation and enhances their immunosuppression activity by inducing the production of Il10 and TGF-β, hence, Treg recruitment [ 164 ].…”
Section: Survival Of Cancer Cells In the Metastatic Environmentmentioning
confidence: 99%